PENGEMBANGAN MEDIA GAMBAR DENGAN MENGGUNAKAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA - Resa Kurniawati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the implementation of the integration of Islamic values in the learning process at SDN 1 Cacaban Cipongkor. The focus of the research is directed at the efforts of teachers in designing and conducting learning that eliminates the dichotomy between science and Islamic religion. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation of learning devices (lesson plans). The results show that teachers at SDN 1 Cacaban have updated the curriculum by integrating Islamic values into various subjects, especially science. This integration is evident when teachers relate the scientific material on the growth and development of living beings with Qur'anic verses about the creation of humans, making the learning more comprehensive and meaningful. These findings emphasize the importance of scientific integration in primary education to shape students who are faithful, knowledgeable, and possess noble character.